2022
DOI: 10.1038/s41598-022-08421-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking assisted biological functions and phytochemical screening of Amaranthus lividus L. extract

Abstract: In this study, the phytochemical content of Amaranthus lividus extract and its multi-biological activities were investigated. Total protein, phenol, flavonoid, saponin and condensed tannin contents were determined for phytochemical analysis. In addition, GC–MS and HPLC analyzes were carried out for the determination of the active components of the extract. In determining the multi-biological activities, radical scavenging, anti-mutagenic, anti-proliferative and anti-microbial activities of the extract were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…Figure 1 shows the best docked complex for phytol, ß-Caryophyllene and 3,3-Dimethyl-1,2,4-cyclopentanetrione. According to a study by Durhan and friends, phytol acts as their molecular docking studies for antibacterial activity which was found inside the A.lividus [9]. In their research paper, it was revealed that the phytol was capable to interact with protein aquaporin-z of bacteria with binding energy of -5.21 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the best docked complex for phytol, ß-Caryophyllene and 3,3-Dimethyl-1,2,4-cyclopentanetrione. According to a study by Durhan and friends, phytol acts as their molecular docking studies for antibacterial activity which was found inside the A.lividus [9]. In their research paper, it was revealed that the phytol was capable to interact with protein aquaporin-z of bacteria with binding energy of -5.21 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…The free radical scavenging capacity of VOA was generally higher than that of VOR. The high free radical scavenging potential of VOA might be due to its main components of olefins and ketones, including phytol, spathulenol, and neophytadiene, which were the effective free radical scavengers 35 38 . VOR had the capacity to suppress the influence of free radicals, might be connected with its certain antioxidant alkynes and olefins such as Panaxynol and β-Bisabolene, which were the main components of VOR, and able to prevent oxidative damage because of their reducing ability 29 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Scoring functions were employed to evaluate and rank the poses produced throughout the docking procedure. These functions gauge the binding free energy or affinity between the ligand and receptor (Durhan et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%